Hanzi write it right / Ting Hie-Ling ...[et al.] - Ting, Hie-Ling; Ch’ng, Looi-Chin; Ibrahim, Norizuandi; Engkamat, Adeline (Akademi Pengajian Bahasa, 2019)
Learning a logograph writing system like Mandarin requires a completely different set of metalinguistic knowledge compared to learning English and Malay which share the same writing system, alphabetical writing system. Mandarin writing system does not allow deconstruction of letters to form different syllabus or phonemes like as in English and Malay. In Mandarin, a simple change of a stroke in a word might change the word and its meaning entirely. Thus, learning to write Mandarin correctly could be the toughest task in Mandarin learning especially non-native learners. To ease this problem, Hanzi Write It Right provides a simple, fun and self-directed learning digital platform to allow learners to practice Mandarin stroke writing. Feedbacks given in the app enable learners to make complicated strokes writing learning to become an easy and more comprehensive experience. Apart from enhancing their accuracy in stroke writing, it also increases their vocabulary knowledge which is crucial in Mandarin learning.